2021
DOI: 10.3390/pathogens10121636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Influenza Virus/Host Interplay

Abstract: Cigarette smoking has been shown to increase the risk of respiratory infection, resulting in the exacerbation of infectious disease outcomes. Influenza viruses are a major respiratory viral pathogen, which are responsible for yearly epidemics that result in between 20,000 and 50,000 deaths in the US alone. However, there are limited general summaries on the impact of cigarette smoking on influenza pathogenic outcomes. Here, we will provide a systematic summarization of the current understanding of the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 99 publications
1
10
0
Order By: Relevance
“…Reduced smoking prevalence-smoking leads to inflammation and is a risk factor in influenza mortality [105][106][107].…”
Section: Factors Increasing Ewm With Time Factors Reducing Ewm With Timementioning
confidence: 99%
“…Reduced smoking prevalence-smoking leads to inflammation and is a risk factor in influenza mortality [105][106][107].…”
Section: Factors Increasing Ewm With Time Factors Reducing Ewm With Timementioning
confidence: 99%
“…As such, it’s possible the water insoluble particles or the combination with soluble components are necessary to induce weight loss. For CSE exposure length, previous studies have shown that there is a difference in pro-inflammatory cytokine response profiles depending on CS exposure of less than or greater than 2 weeks ( 66 ). It is possible that CSE exposure more than 2 weeks could have yielded a more significant effect on morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infections cause significant morbidity and mortality worldwide, both in the form of primary infections (e.g., pneumonia) as well as exacerbations (worsening of symptoms) of chronic lung conditions such as COPD [163]. Cigarette smoke is well described to be a key risk factor for numerous infectious diseases, including latent and active tuberculous [164] as well as increased risk of severe influenza [165][166][167][168]. Evidence that cannabis smoke alters susceptibility to respiratory infection is lacking but its overall effect on immune function as noted above suggests the cannabis smoking may predispose susceptible individuals to pulmonary infections, including those that are immune compromised by human immunodeficiency virus (HIV) or cancer chemotherapy [133,169].…”
Section: Respiratory Infectionsmentioning
confidence: 99%